Women and the Automobile in Sweden - Polk, Merritt (Proceedings from the Annual Transport Conference at Aalborg University, 1997)
In a car advertisement series for Peugeot that ran in the spring of 1997 in DN, GP and SvD, the car was depicted as a symbol of nature, explicitly stated in the caption to the photographs. What the photographs depict are transformations of the human body into a car, in five consecutive frame shots. The five series or transformations use the symbol of the body to represent aesthetic perfection and strength. The ads are sensual and colorful, depicting the car as being a given part of nature as much as humans are a part of nature. What is so interesting about this series is the fact that men and women’s bodies are used so differently, with the male chest being transformed into a motor and the woman’s hips, torso, and legs being transformed into contours of the car body parts. Men’s bodies represent predominantly strength, while women’s bodies represent aesthetic sensuality. The explicitness and clearly separate images that men and women’s body refers to in these advertisements show the continued importance of sexual images and their associations to the automobile.